Myostatin as a Prognostic Biomarker in Hepatic Cirrhosis Patients with Sarcopenia - Rizki Aliana Agustina; Suyata (GoAcademica Research & Publishing, 2023)
Cirrhosis represents the advanced stage of numerous chronic liver conditions. Sarcopenia is a frequently overlooked complication in cirrhotic patients, resulting from factors such as insufficient protein intake, malabsorption, diminished muscle growth, and increased muscle breakdown. Sarcopenia is a multifaceted, chronic condition associated with elevated risks of morbidity and mortality. In the field of hepatology, sarcopenia is typically described as a phenotypic indication of muscle mass loss, affecting approximately 30-70% of liver cirrhosis patients. Sarcopenia has been scientifically linked to an increased risk of falls, reduced quality of life, the emergence of acute decompensated liver failure, and mortality in cirrhotic patients. Myostatin, classified as a cytokine within the transforming growth factor beta (TGF-β) family, is recognized for its role in disrupting protein synthesis. It functions as a negative regulator of muscle growth, inhibiting myogenesisand is linked to the onset of sarcopenia. Extensive literature supports the prognostic importance of sarcopenia in cirrhosis, and serum myostatin levels have the potential to serve as a valuable biomarker. Elevated myostatin concentrations have been linked to the presence of sarcopenia and decreased survival rates in individuals diagnosed with liver cirrhosis.